Financial development and economic growth : an empirical evidence from Malaysia - Low, Siew Phin (2005)
This study examined the relationship between the financial development and economic growth in Malaysia for the period after financial crisis (1997-2004). By using the multivariate cointegration methodology, this study documented the evidence of long run relationships among the economy growth (IPI), financial development (TC) and the interest rate (IR) in Malaysia after the financial crisis. The results of this paper documented that there is a long run relationship among the three variables after evident by the Johansen (1998) and Johansen and Johansen and Juselius (1990) cointegration test. The Vector Error-Correction Model (VECM) was carried out and found that the economy growth (lPI) is Granger caused financial development (TC) in the case of Malaysia in this sample period. At the same time, the results also showing another two single direction causality from financial development to the changes of interest rate and from changes of interest rate to the economy growth. An interesting finding from this study is there is bi-direction causality between the financial growth and the interest rate changes.